UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN PIDADA MERAH (Sonneratia caseolaris L) PADA MENCIT PUTIH (Mus musculus L) - Siti Jubaidah; Eka Siswanto Syamsul; Supomo Supomo (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
The leaves of the red pidada plant (Sonneratia caseolaris L.) are traditionally used by the people of Kalimantan to mix cold powder, treat wounds and have antioxidant properties. The aim was to determine the symptoms of acute toxicity and lethal dose of 50 ethanol extract of red pidada leaf (Sonneratia caseolaris L.) against white mice. Methods: This study used 20 rats which were divided into four groups and given a graded dose of 0.65 g/kgBW, 1.3 g/kgBW, 2.6 g/kgBW, and 5.2 g/kgBW ethanol extract of red pidada leaf with two oral administrations then observed for symptoms of toxicity and the number of deaths in each test animal after 24 hours, then observations were made. body weight for 14 days without treatment. The results showed that the apparent LD50 was: >5.2g/kgBB. Clinical symptoms observed in mice were decreased motor activity at the highest dose and increased grooming frequency. The LD50 of the ethanol extract of red pidada leaves is in the mild toxic category (5-15 g/kgBW).